2001
DOI: 10.1021/jo010579z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoquinolines and Pyridines by the Palladium/Copper-Catalyzed Coupling and Cyclization of Terminal Acetylenes and Unsaturated Imines:  The Total Synthesis of Decumbenine B

Abstract: Monosubstituted isoquinolines and pyridines have been prepared in good to excellent yields via coupling of terminal acetylenes with the tert-butylimines of o-iodobenzaldehydes and 3-halo-2-alkenals in the presence of a palladium catalyst and subsequent copper-catalyzed cyclization of the intermediate iminoalkynes. In addition, isoquinoline heterocycles have been prepared in excellent yields via copper-catalyzed cyclization of iminoalkynes. The choice of cyclization conditions is dependent upon the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(63 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…A more comprehensive study showed that microwaves heating gave comparable or better yields in reduced reaction times (Scheme 8) [17]. The product derived from a 5-exo-dig cyclization mode has never isolated or Isoquinoline heterocycles have been also prepared in excellent yields via copper-catalyzed cyclization of tert-butylimine derivatives of 2-alkynylbenzaldehydes [18]. Dirhodium acetate and silver triflates cooperatively catalyzed tandem cyclization/three-component reactions of 2-alkynylarylaldimines with diazo compounds and water or alcohols afforded 1,2-dihydroisoquinolines bearing a-hydroxyl-b-amino carboxylate skeleton in high yield [19].…”
Section: Resultsmentioning
confidence: 99%
“…A more comprehensive study showed that microwaves heating gave comparable or better yields in reduced reaction times (Scheme 8) [17]. The product derived from a 5-exo-dig cyclization mode has never isolated or Isoquinoline heterocycles have been also prepared in excellent yields via copper-catalyzed cyclization of tert-butylimine derivatives of 2-alkynylbenzaldehydes [18]. Dirhodium acetate and silver triflates cooperatively catalyzed tandem cyclization/three-component reactions of 2-alkynylarylaldimines with diazo compounds and water or alcohols afforded 1,2-dihydroisoquinolines bearing a-hydroxyl-b-amino carboxylate skeleton in high yield [19].…”
Section: Resultsmentioning
confidence: 99%
“…Solvents for column chromotography, ethyl acetate and light petroleum were distilled in a rotary evaporator. The following compounds were prepared according to known literature methods: methylenespiropentane (11), [4] 2,3-dihydrobenzo [1,4]dioxine-6-carbaldehyde, [12] benzo [1,3]dioxole-4-carbaldehyde, [12] (3,4-dimethoxyphenyl)methanol, [13] piperonylic alcohol, [14] (2,3-dihydrobenzo [1,4]dioxin-6-yl)-methanol, [14] (benzo [1,3]dioxol-4-yl)methanol, [15] 2-iodo-4,5-dimethoxybenzyl alcohol (33c), [16] (6-iodobenzo [1,3]dioxol-5-yl)-methanol (33d), [17] (5-iodobenzo [1,3]dioxol-4-yl)methanol (33g), [15] 5-chloromethyl-6-iodobenzo [1,3]dioxole, [18] 2-iodobenzyl methanesulfonate, [19] (benzyl)(2-iodobenzyl)amine (33b), [20] 2-(2-iodophenyl)ethanol (40). [21] Heck Reaction of Methylenespiropentane (11) with Iodobenzene (12).…”
Section: Methodsmentioning
confidence: 99%
“…[28] Palladium-catalyzed coupling of vinylic imines with terminal alkynes followed by subsequent copper-catalyzed cyclization gave aryl-, vinyl-, and alkyl-substituted pyridines in moderate yields. Significantly, this method was extended to the synthesis of alkaloid decumbenine B and various other isoquinolines.…”
Section: Wwwchemeurjorg Recent Advances In Pyridine Synthesismentioning
confidence: 99%
“…The [4 + 2] palladium-/copper-catalyzed route to pyridines. [28] Scheme 18. The [4 + 2] rhodium-/palladium-catalyzed route to pyridines.…”
Section: Wwwchemeurjorg Recent Advances In Pyridine Synthesismentioning
confidence: 99%